Short- and long-term eccentric training-induced adaptations - Coratella, G. (8th International Congress Mountain Sport & Health. Updating Study and Research from Laboratory to Field. 7-8 November 2019, Rovereto (TN) - Italy. Programme and Book of Abstracts, 2019)
Eccentric exercise is widely implemented in training routing, both to improve performance and in rehabilitation. Notwithstanding, it is well known that a first eccentric session results typically in exercise-induced muscle damage, whatever the eccentric exercise modality (e.g. isokinetic, dynamic-constant external load or iso-inertial eccentric exercise). Indeed, the forcibly-lengthened sarcomeres that are ruptured by the active muscle lengthening, trigger a reparation process that could last several days. Such a recovery process can be monitored using different non-invasive markers, as strength loss, decrease in passive range of movement, increase in muscle girth, echo-intensity, increase in creatin-kinase or myoglobin blood concentration, acute shift in optimum angle towards longer muscle length and delayed-onset of muscle soreness. Particularly, this last may be an economic, simple and effective method to evaluate the time-course of the recovery process. Quantifying the delayed-onset of muscle soreness require few important familiarization steps to avoid the subjects misunderstand or falsify the measure. Exerciseinduced muscle damage is more marked when eccentric exercise is performed with highvolume and/or high-intensity, high-velocity, or at long vs short muscle length. Thus, manipulating these factors and understanding how to monitor the recovery process is warranted in both training and rehabilitation periods. Lastly, a first bout of eccentric exercise, albeit inducing muscle damage, protects from a following eccentric bout performed on a subsequent session. This phenomenon has been named "repeated bout effect" and it was proposed to depend on mechanical, cellular, inflammatory and/or neural mechanisms. Therefore, safely implementing eccentric exercise within a training or rehabilitation routine should take into account the acute and the long-lasting muscle response to the eccentric stimulus.